An analysis of Ofsted inspection reports for children's social care services in England. Issue 2 (2nd September 2018) - Hood, Rick; Nilsson, David; Habibi, Ruth
Abstract: The Office for Standards in Education, Children's Services and Skills (Ofsted) is responsible for inspecting services that care for children and young people in England and Wales. This paper presents findings from an independent study of Ofsted inspections into children's social care in England, covering reports under three inspection frameworks during the period 2009 to 2016. The research aimed to identify the main themes of recommendations made in Ofsted reports and to explore similarities and differences between frameworks and between local authorities. The methodological approach was document analysis. A stratified sample of 60 reports was prepared on the basis of inspection framework and local authority characteristics such as local deprivation, Ofsted rating, and urban/rural category. A thematic analysis was conducted of the recommendations in each report, with emerging themes subjected to an iterative process of coding and categorization. The findings identified nine categories of themes, the most common of which were performance management, casework, oversight of practice, and multiagency working. Overall, the recommendations were strongly oriented towards process issues and compliance with standards. Recommendations were found to differ somewhat between inspection frameworks but remained largely consistent between local authorities with different characteristics. The paper concludes by examining the implications of findings for the current regulatory framework in children's social care.